Evaluation of Apically Extruded Debris Using Continuous Rotation, Reciprocation, or Adaptive Motion - Sen,Ozgur Genc (2018)
Abstract The aim of this study was to compare the amount of apically extruded debris during root canal instrumentation using ProTaper Next (PTN), Twisted File (TF) Adaptive, and Reciproc instruments. Forty-five extracted human maxillary canines were selected and randomly assigned into 3 groups. The root canals were prepared using PTN instruments with continuous rotation (n=15), TF Adaptive instruments with adaptive motion (n=15), Reciproc instruments with reciprocating motion (n=15). During the preparations, canals were irrigated using distilled water and material extruded apically was collected in pre-weighed Eppendorf tubes. After a 5-day drying period in an incubator, the tubes were weighed and the dry weight of the extruded debris was calculated. Data distributions were assessed via the Shapiro-Wilk test, and groups were compared via the Kruskal-Wallis test. The greatest amount of debris extruded by TF Adaptive and the least by PTN, but the difference was insignificant between groups (p=0.259). All instrumentation systems were associated with debris extrusion.